Bionic iontronics based on nano-confined structures - Qian, Han; Wei, Di; Wang, Zhonglin (Nano research, 2023)
The Moore’s law in silicone-based electronics is reaching its limit and the energy efficiency of the most sophisticated electronics to mimic the iontronic logic circuit in single-celled organisms is still inferior to their natural counterpart. Unlike electronics, iontronics is widely present in nature, and provides the fundamentals for many life activities through the transmission and conversion of information and energy via ions. Moreover, as nanotechnology and fabrication processes continue to advance, highly efficient iontronics could be enabled by creation of asymmetry from nano-confined unipolar ion transport through various nanohierarchical structures of materials. The introduction of bionic design and nanostructures has made it possible for ions to demonstrate numerous anomalous behaviours and entirely new mechanisms, which are governed by complex interfacial interactions. In this review, we discuss the origins, development, mechanism, and applications of bionic iontronics and analyze the unique benefits as well as the practicality of iontronics from a variety of perspectives. Iontronics, as an emerging field of research with innumerable challenges and opportunities for exploring the theory and applications of ions as transport carriers, promises to provide new insights in many subjects covering energy and sensing, etc., and establishes a new paradigm in investigating the ionic-electric signal transduction interface for futuristic iontronic logic circuit and neuromorphic computing.